Firing Patterns of Human Biceps Brachii Motor Units During Isotorque Ramp-and-Hold Movements in the Elbow Joint - Tal’nov, A.N.; Tomiak, T.; Maznychenko, A.V.; Dovgalets, G.V.; Kostyukov, A.I. (Нейрофизиология, 2014)
The activity of 18 motor units (MUs) of m. biceps brachii was studied in four adults during
high-amplitude isotorque ramp-and-hold movements in the elbow joint. The recorded MUs
had low isometric thresholds (below 6% of maximal voluntary contraction). During the
examined movement, MUs of group I responded to application of subthreshold loads by
increases in their firing rates, MUs of group II reacted to suprathreshold loads by decreases
in the attained activity level, and background firing of MUs of group III at application of
suprathreshold loads did not change. Dependences between the joint angle and firing rate, as
well as between the velocities of these parameters, were positive in group I MUs and negative
in those of group II. A decrease in the firing rate of MUs during flexion movements is likely
to be related to nonlinear effects during the torque generation by the elbow flexors due to the
specificity of geometrical arrangement of MU fibers with respect to the joint. Досліджували активність 18 рухових одиниць (РО) m. biceps
brachii у чотирьох дорослих чоловіків під час високоамплітудних згинальних і розгинальних рухів (по трапецієподібній траєкторії) у ліктьовому суглобі. Під час ізометричних
зусиль зареєстровані РО мали низькі пороги активації (менше 6 % сили максимального довільного скорочення м’язів).
Впродовж руху РО групи I реагували на підпорогові навантаження, збільшуючи частоту активності, а РО групи ІІ реагували на надпорогові навантаження зменшенням досягнутого рівня активності. Фонова активність у РО групи ІІІ при
прикладанні надпорогових навантажень не змінювалась. Залежності як між суглобним кутом і частотою активності РО,
так і між відповідними швидкісними параметрами були позитивними в групі І та негативними в групі ІІ. Зменшення
частоти імпульсації РО в перебігу згинальних рухів, ймовірно, пов’язано з нелінійною зміною моменту сили згиначів
ліктя, зумовленої геометричним розташуванням цих м’язів.